Heterotopic in spontaneous ruptured pregnancy with a living birth term: a case report in Madagascar - Housni, Ibrahim; Randriamahavonjy, Romuald; Ratsiatosika, Tanjona Andriamanetsiarivo; Solange, Rasoanandrianina Bienvenue; Abdallah, Abasse Baco; Rakotovao, Andrianampanalinarivo Hery (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Heterotopic pregnancy is defined as the coexistence of an intrauterine pregnancy (UGI) and an ectopic pregnancy (EUS), regardless of its location. It is a rare pathology. Here, we report the case of a 29-year-old patient who had a heterotopic in spontaneous pregnancy complicated by hemoperitoneum at 7 weeks of amenorrhea. A laparotomy with salpingectomy was performed. The result was favourable with a live birth with 37 SA of the GIU. A heterotopic pregnancy must always be eliminated in the presence of acute pelvic pain in the pregnant woman. Laparotomy is a therapeutic alternative if laparoscopy is not available.